Religious Escalation Strategies to Strengthen Inmates’ Spiritual Values at the Mesuji Police Correctional Institution - Ro’uf, Muhamad Ghufron; Setiawan, Dedi; Suhono, Suhono (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to examine the strategy of religious escalation efforts in enhancing religious values among inmates at the Correctional Facility of Polres Mesuji. The background of this research is based on the importance of religious development as a part of moral and spiritual rehabilitation to help inmates lead better lives after serving their sentences.The research uses a qualitative method with data collection techniques including observation, in-depth interviews, and documentation. The informants consist of correctional officers, religious leaders, and inmates who participate in religious development programs. Data analysis was conducted through data reduction, data presentation, and drawing conclusions in a descriptive manner.The findings show that the religious escalation strategy implemented at the Polres Mesuji correctional facility includes several steps: (1) strengthening routine religious programs such as Qur'anic study sessions, congregational prayers, and Islamic lectures; (2) active involvement of local religious figures as spiritual mentors; (3) personal and religious counseling approaches; and (4) motivation and rewards for inmates who demonstrate positive behavioral changes. This strategy has proven effective in building inmates' spiritual awareness, improving discipline, and reinforcing religious values such as honesty, responsibility, and repentance.This research recommends Enriches the body of knowledge in the fields of criminology, religious psychology, and religious education, particularly in the context of inmate rehabilitation.Offers a new perspective on the escalation of religious effort as a strategy for moral and spiritual development within correctional institutions.